Biochar / prussian blue composite and method for preparing the same

CN122999136APending Publication Date: 2026-10-30HUNAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610082260.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-01-21
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

本发明提供了一种生物炭/普鲁士蓝复合材料的制备方法,将改性生物炭和普鲁士蓝混合进行球磨,第一,可以将材料细化至纳米尺度,增大比表面积;第二,改善了复合材料的孔隙结构,使其具有发达的中孔网络,为重金属离子提供充足的扩散通道,提高了传质速率;第三,通过机械力化学效应,有效打破生物炭的惰性表面,增加其表面活性位点,提高石墨化程度,同时诱导生物炭和普鲁士蓝界面发生化学键合,形成具有协同增强效应的高稳定性复合结构,从而极大地促进普鲁士蓝颗粒在生物炭载体上的均匀分散与牢固复合,最终制得吸附效果好、稳定性高、易于回收的生物炭/普鲁士蓝复合材料。本发明的制备方法,采用的原料来源广、价格低廉,制备过程无需额外投加化学药剂,有效防止二次污染,且制备工艺简单,易于实现规模化生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999136A_ABST
    Figure CN122999136A_ABST
Patent Text Reader

Abstract

The application discloses a kind of biochar / prussian blue composite material and preparation method thereof, the preparation method includes the following steps: biochar is modified with acid, and obtain modified biochar;Modified biochar and prussian blue are mixed, ball milling is carried out, and biochar / prussian blue composite material is obtained.The preparation method of the application, by the mechanical chemical effect of ball milling process, effectively break the inert surface of biochar, increase its surface active site, improve the graphitization degree, simultaneously induce the interface of biochar and prussian blue to occur chemical bonding, form the high stability composite structure with synergistic enhancement effect, greatly promote prussian blue particles on the uniform dispersion and firm composite of biochar carrier, so that the biochar / prussian blue composite material with good adsorption effect, high stability, easy to recover is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of environmental protection, specifically relating to a biochar / Prussian blue composite material and its preparation method. Background Technology

[0002] With rapid industrialization, heavy metal pollution in water bodies has become an increasingly serious problem. Among numerous water treatment technologies, adsorption is widely used due to its advantages such as high efficiency, economy, and minimal secondary pollution. Therefore, developing high-performance and highly stable adsorption materials has become a core research direction in this field.

[0003] Prussian blue, a classic microporous coordination polymer, possesses a unique face-centered cubic lattice structure with uniformly sized pores, exhibiting excellent selective adsorption potential for heavy metal ions of specific sizes (such as cesium and thallium). However, Prussian blue materials are typically nanoscale powders, which are prone to agglomeration in practical applications and difficult to separate from treated water, posing a risk of secondary pollution and severely limiting their engineering applications. Loading Prussian blue onto large-scale supports is one effective strategy to address this problem. Biochar, as a widely available, inexpensive, and environmentally friendly porous carbon material, is considered an ideal candidate for a support. However, traditional liquid-phase loading or physical mixing methods often fail to achieve efficient, uniform, and stable loading of Prussian blue within the pores of biochar, resulting in insufficient exposure of adsorption sites and weak intercomponent bonding in the composite material, ultimately affecting its adsorption capacity and stability. Therefore, developing a biochar / Prussian blue composite material with good adsorption performance, high stability, and easy recovery has significant theoretical and applied value for promoting the innovative development of high-performance and high-stability adsorbent materials. Summary of the Invention

[0004] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a biochar / Prussian blue composite material with good adsorption effect, high stability and easy recovery and its preparation method.

[0005] To solve the above-mentioned technical problems, the present invention adopts the following technical solution.

[0006] A method for preparing a biochar / Prussian blue composite material includes the following steps: S1. Mix biochar with an acidic solution and perform acid modification to obtain modified biochar; S2. Mix the modified biochar and Prussian blue obtained in step S1 and ball mill them to obtain a biochar / Prussian blue composite material.

[0007] In a further improvement to the above preparation method, in step S2, the mass ratio of the modified biochar to Prussian blue is 0.5 to 2:1.

[0008] In a further improvement to the above preparation method, in step S2, the mass ratio of the modified biochar to Prussian blue is 0.5 to 1:1.

[0009] In a further improvement to the above preparation method, in step S2, the ball milling time is 3h to 5h, the ball milling speed is 300rpm to 400rpm, and the ball-to-material ratio is 50 to 100:1. In a further improvement to the above preparation method, in step S1, the concentration of the acidic solution is 1 mol / L to 2 mol / L, the mass-to-volume ratio of the biochar to the acidic solution is 1 g: 20 mL to 40 mL, and the acidic solution is a hydrochloric acid solution or a sulfuric acid solution.

[0010] In a further improvement to the above preparation method, in step S1, the mixing is carried out under ultrasonic conditions for 5 min to 25 min, the acid modification is carried out under stirring conditions for 300 rpm to 650 rpm for 2 h, and the acid modification is followed by the following treatment: washing and drying the product.

[0011] In a further improvement to the above preparation method, in step S1, the biochar is prepared by carbonizing the biomass material under a nitrogen atmosphere or an inert atmosphere to obtain biochar.

[0012] In a further improvement to the above preparation method, the carbonization temperature is 400℃~900℃, the carbonization time is 1h~3h, and the heating rate during the carbonization process is 5℃ / min~10℃ / min.

[0013] The above preparation method is further improved in that the carbonization temperature is 700℃~900℃; the biomass material is further treated as follows before use: the biomass material is washed, dried, crushed and sieved, and the biomass material is at least one of watermelon rind, coconut shell and shrimp shell.

[0014] As a general technical concept, the present invention also provides a biochar / Prussian blue composite material prepared by the above-described preparation method.

[0015] Compared with the prior art, the advantages of the present invention are as follows: This invention provides a method for preparing a biochar / Prussian blue composite material. Modified biochar and Prussian blue are mixed and ball-milled. First, this refines the material to the nanoscale, increasing the specific surface area. Second, it improves the pore structure of the composite material, giving it a well-developed mesoporous network, providing ample diffusion channels for heavy metal ions and increasing the mass transfer rate. Third, through mechanochemical effects, the inert surface of the biochar is effectively broken, increasing its surface active sites and improving the degree of graphitization. Simultaneously, it induces chemical bonding at the interface between the biochar and Prussian blue, forming a highly stable composite structure with a synergistic enhancement effect. This greatly promotes the uniform dispersion and firm bonding of Prussian blue particles on the biochar carrier, ultimately yielding a biochar / Prussian blue composite material with good adsorption performance, high stability, and easy recovery. The preparation method of this invention uses widely available and inexpensive raw materials, requires no additional chemical reagents during the preparation process, effectively prevents secondary pollution, and has a simple preparation process that is easy to scale up for production. Attached Figure Description

[0016] Figure 1 Transmission electron microscopy (TEM) images of modified biochar, Prussian blue, and biochar / Prussian blue composite materials in Example 1 of this invention.

[0017] Figure 2 The X-ray diffraction patterns are those of the modified biochar, biochar / Prussian blue composite material in Example 1, and the biochar / Prussian blue milled composite material in Comparative Example 1.

[0018] Figure 3 The diagram shows the pore size distribution of the biochar / Prussian blue composite material in Examples 1, 3, and 4 of this invention.

[0019] Figure 4 The image shows the removal effect of the biochar / Prussian blue composite material in Example 1 of this invention on different heavy metals.

[0020] Figure 5 The images show the thallium removal effects of Prussian blue in Example 1, biochar / Prussian blue composite material, and biochar / Prussian blue grinding composite material in Comparative Example 1.

[0021] Figure 6 The image shows the dissolution effect of the biochar / Prussian blue composite material and Prussian blue in Example 1 of this invention. Detailed Implementation

[0022] The present invention will be further described below with reference to the accompanying drawings and specific preferred embodiments, but this does not limit the scope of protection of the present invention. All materials and instruments used in the following embodiments are commercially available.

[0023] Example 1: A method for preparing a biochar / Prussian blue composite material according to the present invention includes the following steps: (1) Pretreatment of waste watermelon rinds: Wash the discarded watermelon rinds, dry them at 85°C for 24 hours, crush the samples using a plant-based crusher for 3 minutes, and pass them through a 100-mesh sieve (0.149 mm) to obtain watermelon rind powder.

[0024] (2) Preparation of biochar: The watermelon rind powder obtained in step (1) was placed in a tube furnace and heated from room temperature to 600 ℃ at a heating rate of 5 ℃ / min under the protection of flowing nitrogen and carbonized at a constant temperature for 2 h. After natural cooling, it was taken out to obtain watermelon rind biochar.

[0025] (3) Modification of biochar: Take 1 g of watermelon rind biochar obtained in step (2) and add it to 40 mL of hydrochloric acid solution with a concentration of 2 mol / L. After ultrasonic dispersion for 10 min, stir for 2 h at room temperature and 350 rpm for acid modification. Filter the treated mixed solution and wash the obtained solid material with deionized water until neutral. Dry at 60 ℃ for 24 h to obtain modified biochar.

[0026] In this step, ultrasonic dispersion can be performed for 5 to 25 minutes.

[0027] (4) Take 1 g of the modified biochar obtained in step (3) and 1 g of Prussian blue and place them in a ball milling device, add 200 g of ball milling beads, and ball mill for 3 h at room temperature and a speed of 350 rpm to obtain the biochar / Prussian blue composite material.

[0028] Comparative Example 1 A biochar / Prussian blue grinding composite material is prepared in a manner that is basically the same as the preparation method of the biochar / Prussian blue composite material in Example 1. The only difference is that in step (4), ball milling is not performed, but the modified biochar and Prussian blue are mixed and ground evenly.

[0029] Example 2 A method for preparing a biochar / Prussian blue composite material according to the present invention includes the following steps: (1) Pretreatment of waste watermelon rinds: Wash the discarded watermelon rinds, dry them at 85°C for 24 hours, crush the samples using a plant-based crusher for 3 minutes, and pass them through a 100-mesh sieve (0.149 mm) to obtain watermelon rind powder.

[0030] (2) Preparation of biochar: The watermelon rind powder obtained in step (1) was placed in a tube furnace and heated from room temperature to 800 ℃ at a heating rate of 5 ℃ / min under the protection of flowing nitrogen and carbonized at a constant temperature for 2 h. After natural cooling, it was taken out to obtain watermelon rind biochar.

[0031] (3) Modification of biochar: Take 1 g of watermelon rind biochar obtained in step (2) and add it to 40 mL of hydrochloric acid solution with a concentration of 2 mol / L. After ultrasonic dispersion for 10 min, stir for 2 h at room temperature and 350 rpm for acid modification. Filter the treated mixed solution and wash the obtained solid material with deionized water until neutral. Dry at 60 ℃ for 24 h to obtain modified biochar.

[0032] (4) Take 0.5 g of the modified biochar obtained in step (3) and 1 g of Prussian blue and place them in a ball milling device, add 150 g of ball milling beads, and ball mill for 3 h at room temperature and a speed of 350 rpm to obtain the biochar / Prussian blue composite material, denoted as A.

[0033] In this embodiment, biochar / Prussian blue composite materials with different carbonization temperatures were also prepared. The preparation method was basically the same as that of biochar / Prussian blue composite material (A) in this embodiment. The only difference was that in step (2), the carbonization temperatures were 400 ℃ and 600 ℃, respectively. The corresponding biochar / Prussian blue composite materials were denoted as A1 and A2, respectively.

[0034] In this embodiment, biochar / Prussian blue composite materials with different amounts of modified biochar were also prepared. The preparation method was basically the same as that of the biochar / Prussian blue composite material (A) in this embodiment. The only difference was that in step (4), the amount of modified biochar was 1g and the amount of ball milling beads was 200g. The corresponding biochar / Prussian blue composite material was denoted as B1.

[0035] In this embodiment, biochar / Prussian blue composite materials with different amounts of modified biochar and Prussian blue were also prepared. The preparation method was basically the same as that of the biochar / Prussian blue composite material (A) in this embodiment. The only difference was that in step (4), the amount of modified biochar was 1g and the amount of Prussian blue was 0.5g. The corresponding biochar / Prussian blue composite material was denoted as B2.

[0036] The thallium removal effect of the biochar / Prussian blue composite materials (A, A1, A2, B1, B2) in this embodiment was tested. Specifically, in the application to treat thallium-containing wastewater, five 50 mL solutions of thallium-containing (Tl(I)) with a concentration of 1 mg / L were placed in 100 mL beakers, and 10 mg of biochar / Prussian blue composite materials (A, A1, A2, B1, B2) were added to each. Adsorption was carried out at 350 rpm and 25 °C for 2 h to remove thallium from the water.

[0037] After 2 hours of adsorption, the thallium removal rates of the biochar / Prussian blue composite materials (A, A1, A2, B1, B2) were 98.55%, 88.01%, 94%, 95.88%, and 93.25%, respectively. It is evident that the preparation method of the biochar / Prussian blue composite material of the present invention, when the carbonization temperature of the biochar is 800℃ and the mass ratio of modified biochar to Prussian blue is 0.5:1, can obtain the biochar / Prussian blue composite material with the best thallium adsorption performance.

[0038] Example 3 The preparation method of the biochar / Prussian blue composite material of the present invention is basically the same as that of the preparation method of the biochar / Prussian blue composite material in Example 1, except that: in step (1), watermelon rind is replaced with coconut shell.

[0039] Example 4 The preparation method of the biochar / Prussian blue composite material of the present invention is basically the same as that of the preparation method of the biochar / Prussian blue composite material in Example 1, except that in step (1), watermelon rind is replaced with waste shrimp shell.

[0040] Transmission electron microscopy (TEM) imaging was performed on the modified biochar, Prussian blue, and biochar / Prussian blue composite material in Example 1. The results are as follows: Figure 1 As shown. Figure 1 Transmission electron microscopy (TEM) images of modified biochar, Prussian blue, and biochar / Prussian blue composite materials in Example 1 of this invention. Figure 1 In the images, (a) is modified biochar, (b) is Prussian blue, and (c) is a biochar / Prussian blue composite material. Figure 1 As shown in (a), the watermelon rind powder has been completely carbonized into biochar, which exhibits distinct graphite striations, indicating a high degree of graphitization. Figure 1 As shown in (b) and (c), ball milling allows the relatively dispersed and easily agglomerated Prussian blue nanoparticles to bind tightly with biochar. At the same time, the supporting effect provided by biochar as a carrier effectively inhibits the agglomeration of Prussian blue.

[0041] Figure 2 These are X-ray diffraction patterns of the modified biochar, biochar / Prussian blue composite material, and the biochar / Prussian blue milled composite material in Example 1 of this invention, and Comparative Example 1. Figure 2 It can be seen that the modified biochar in Example 1, the biochar / Prussian blue composite material, and the biochar / Prussian blue milled composite material in Comparative Example 1 all successfully loaded Prussian blue onto biochar. However, the intensity of the (002) peak (diffraction angle of 26.5°) of the biochar / Prussian blue composite material is much higher than that of the biochar / Prussian blue milled composite material, indicating that the ball milling process increased the bonding force between biochar and Prussian blue and improved the graphitization degree of the material.

[0042] Figure 3 This is a pore size distribution diagram of the biochar / Prussian blue composite material used in Examples 1, 3, and 4 of this invention. Figure 3 As shown, the biochar / Prussian blue composite materials prepared in Examples 1, 3, and 4 all exhibit a concentrated mesoporous distribution, meaning the pore size is mainly distributed in the range of 2–60 nm. The well-developed mesoporous network provides diffusion channels for heavy metal ions, improving the mass transfer rate and overcoming the shortcomings of traditional microporous materials such as high mass transfer resistance, low internal site utilization, and easy clogging. Therefore, the preparation method of this invention, through a unique ball milling process, successfully controls and constructs a biochar / Prussian blue composite material dominated by mesoporous structures.

[0043] Multiple heavy metals (Cu) in the biochar / Prussian blue composite material of Example 1 2+ Zn 2+ Cd 2+ Pb 2+ 、Tl + The adsorption effect was tested, specifically: in 50 mL of Cu-containing solution with a concentration of 1 mg / L... 2+ Solution, Zn 2+ Solution, Cd 2+ Solution, Pb 2 + Solution, Tl + In the solution, 10 mg of the biochar / Prussian blue composite material from Example 1 was added, and adsorption was carried out at 350 rpm and 25 °C for 2 h to complete the removal of heavy metals from the water. Figure 4 Experimental data show that the biochar / Prussian blue composite material of the present invention has a positive effect on Cu. 2+ Zn 2+ Cd 2+ Pb 2+ 、Tl + All five heavy metal ions showed good adsorption effects, and their removal rates were as follows: Cu 2+ (94.80%), Zn 2+ (94.50%), Cd 2+ (95.40%), Pb 2+ (94.90%) and Tl + (95.88%), of which, for Tl + The highest removal rate indicates that the composite material has the best adsorption capacity for thallium. These results collectively demonstrate that the biochar / Prussian blue composite material of this invention possesses efficient and broad removal potential for various heavy metal ions.

[0044] The thallium removal effects of Prussian blue in Example 1, the biochar / Prussian blue composite material, and the biochar / Prussian blue abrasive composite material in Comparative Example 1 were tested, and the results are as follows: Figure 5 As shown, specifically: 10 mg of Prussian blue from Example 1, the biochar / Prussian blue composite material, and the biochar / Prussian blue ground composite material from Comparative Example 1 were added to 50 mL of a thallium-containing solution with a concentration of 1 mg / L. Adsorption was carried out at 350 rpm and 25 °C for 2 h to complete the removal of thallium from the water. The dissolution effects of Prussian blue and the biochar / Prussian blue composite material after 2 h of adsorption are shown below. Figure 6 As shown.

[0045] Figure 5 These are images showing the thallium removal effects of Prussian blue in Example 1, the biochar / Prussian blue composite material, and the biochar / Prussian blue milled composite material in Comparative Example 1. Figure 5 As can be seen, the thallium removal rate of the biochar / Prussian blue composite material in Example 1 was 95.88%, which is much higher than that of Prussian blue alone (56.76%) and the biochar / Prussian blue milled composite material (44.86%). Clearly, the ball milling process used in this invention is not a simple physical mixing process, but rather achieves deep composite and synergistic effect of biochar and Prussian blue through high-intensity mechanical force. This effectively overcomes the problems of easy agglomeration and difficult recovery of pure Prussian blue nanoparticles, as well as the uneven composite and weak binding force of conventional milling methods, thus greatly enhancing the adsorption capacity and selectivity of the composite material.

[0046] Figure 6 The image shows the dissolution effect of the biochar / Prussian blue composite material and Prussian blue in Example 1 of this invention. Figure 6 In the image, (a) is a biochar / Prussian blue composite material, and (b) is Prussian blue. (The image is composed of...) Figure 6 It can be seen that after 2 hours of adsorption testing, the single Prussian blue reaction system exhibited significant blue dissolution, indicating that the material structure was unstable. The biochar / Prussian blue composite material reaction system of this invention remained transparent throughout, with no visible blue dissolution. Therefore, the preparation method of this invention, through ball milling and compounding, firmly anchors Prussian blue onto the biochar support, effectively suppressing the dissolution of iron and cyanide ions in its crystal structure. This not only solves the key bottleneck of Prussian blue as an adsorbent easily causing secondary pollution, but also ensures the environmental friendliness of the adsorption process and the long-term usability of the material.

[0047] The biochar / Prussian blue composite material of the present invention uses a ball milling process to firmly anchor Prussian blue nanoparticles onto a biochar support. The two work synergistically to significantly enhance the adsorption capacity for thallium. Specifically, on the one hand, the high specific surface area and porous structure of the biochar provide a Tl... +It provides an efficient mass transfer channel, enabling it to quickly reach the adsorption site. Simultaneously, the oxygen-containing functional groups on the biochar surface participate in the chemical fixation process, promoting the partial absorption of Tl. + It is transformed into the more chemically stable Tl₂O form; on the other hand, Prussian blue, as the core active component, utilizes its unique crystal structure to transform Tl₂O into a more chemically stable form. + By performing highly selective ion exchange and fixation, and combining physical adsorption with chemical fixation, the thallium fixation capacity of the composite material is greatly enhanced, resulting in advantages such as good adsorption effect, high stability, and easy recycling.

[0048] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make many possible variations and modifications to the technical solutions of the present invention using the methods and techniques disclosed above, or modify them into equivalent embodiments with equivalent changes, without departing from the spirit and technical essence of the present invention. Therefore, any simple modifications, equivalent substitutions, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solutions of the present invention shall still fall within the protection scope of the technical solutions of the present invention.

Claims

1. A method for preparing a biochar / Prussian blue composite material, characterized in that, Includes the following steps: S1. Mix biochar with an acidic solution and perform acid modification to obtain modified biochar; S2. Mix the modified biochar and Prussian blue obtained in step S1 and ball mill them to obtain a biochar / Prussian blue composite material.

2. The method for preparing the biochar / Prussian blue composite material according to claim 1, characterized in that, In step S2, the mass ratio of the modified biochar to Prussian blue is 0.5 to 2:

1.

3. The method for preparing the biochar / Prussian blue composite material according to claim 2, characterized in that, In step S2, the mass ratio of the modified biochar to Prussian blue is 0.5 to 1:

1.

4. The method for preparing the biochar / Prussian blue composite material according to claim 3, characterized in that, In step S2, the ball milling time is 3h to 5h, the ball milling speed is 300rpm to 400rpm, and the ball-to-material ratio is 50 to 100:

1.

5. The method for preparing the biochar / Prussian blue composite material according to any one of claims 1 to 4, characterized in that, In step S1, the concentration of the acidic solution is 1 mol / L to 2 mol / L, the mass-to-volume ratio of the biochar to the acidic solution is 1 g: 20 mL to 40 mL, and the acidic solution is hydrochloric acid solution or sulfuric acid solution.

6. The method for preparing the biochar / Prussian blue composite material according to any one of claims 1 to 4, characterized in that, In step S1, the mixing is performed under ultrasonic conditions for 5 to 25 minutes, and the acid modification is performed under stirring conditions for 300 to 650 rpm for 2 hours. After acid modification... The process includes the following steps: washing and drying the product.

7. The method for preparing the biochar / Prussian blue composite material according to any one of claims 1 to 4, characterized in that, In step S1, the biochar is prepared by carbonizing biomass materials under a nitrogen atmosphere or an inert atmosphere to obtain biochar.

8. The method for preparing the biochar / Prussian blue composite material according to claim 7, characterized in that, The carbonization temperature is 400℃~900℃, the carbonization time is 1h~3h, and the heating rate during the carbonization process is 5℃ / min~10℃ / min.

9. The method for preparing the biochar / Prussian blue composite material according to claim 8, characterized in that, The carbonization temperature is 700℃~900℃; the biomass material also includes the following treatment before use: washing, drying, crushing and sieving the biomass material, wherein the biomass material is at least one of watermelon rind, coconut shell and shrimp shell.

10. A biochar / Prussian blue composite material prepared by the method described in any one of claims 1 to 9.